Комплектний синхронний електропривід з програмним керуванням - Півняк, Г.Г.; Кириченко, В.І.; Кириченко, В.В.; Боровик, Р.О. (Видавничий дім "Академперіодика" НАН України, 2007)
Algorithms of the program control over the feed source of an engine are proposed. The feed source includes gages and two regulators, and the microprocessor control system has two channels for the realization of the algorithms and the compensation of the instability of parameters of the electric drive, respectively.